Wise Reasoning Skill Development as a Goal of Education - Smajović Ibrović, Amina (Context: Journal of Interdisciplinary Studies, 2024)
The first part of the paper attempts to understand the phenomenon of wisdom better and offer a view of the pedagogy of wisdom through three forms of teaching: teaching about wisdom, teaching wisdom, and wise teaching. Starting from the assumption that the goals of teaching wisdom (making correct judgments, having broader insights, distinguishing internal qualities and relationships, accepting, appreciating, and integrating different perspectives) can be achieved through intentional pedagogical action, the paper sought to investigate whether the components of wise reasoning are integrated into the madrasah curriculum. The results showed that the need to enrich curricula with elements of wisdom in Islamic subjects was recognised. However, this dimension is absent in general education subjects. The paper calls for raising awareness of the importance of enriching curricula to develop wisdom. Developing wisdom should be an important goal of education, and it requires appropriate visibility throughout the curriculum.